Wearables in Healthcare: Second EAI International Conference, HealthWear 2020, Virtual Event, December 10-11, 2020, Proceedings - Perego, Paolo; TaheriNejad, Nima; Caon, Maurizio (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2021)
This book constitutes the refereed post-conference proceedings of the Second EAI International Conference on Wearables in Healthcare, HealthWear 2020. Due to COVID-19 pandemic the conference was held virtually. The 16 revised full papers were carefully reviewed and selected from 40 submissions. They focus on wearable devices and systems for healthcare and wellbeing. The papers are organized in topical sections as follows: PPG and algorithms focusing on photoplethysmography, PPG monitoring and cardiorespiratory measurement. The next section focus on IoT and smart sensors  on the use of wearable devices and systems for Internet of Medical Things application. The third section is a new session introducing wearable applications. This track focuses on the intrinsic multidisciplinary of wearable devices, and includes works on methodology and design aspect of wearable research.